1997
DOI: 10.1111/j.1525-1594.1997.tb00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Impacts of Hepatitis Virus Infection in Hemodialysis Patients: Should Liver Biopsy Be Performed Before Renal Transplantation?

Abstract: To evaluate the histologic changes in the livers of renal transplant candidates who were infected with hepatitis viruses, we performed a percutaneous liver biopsy in each of 74 regular hemodialysis patients. Forty percent of them were seropositive for the antibody to hepatitis C virus (anti-HCV) whereas 29.7% had anti-HCV and antibody to hepatitis B surface antigen (antiHBs) concomitantly. Seven (9.5%) were seropositive for only hepatitis B surface antigen HBsAg. Histopathological examination revealed that 30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…In our cohort of 270 cases, only 1 patient showed histological cirrhosis. Except a study by Ozdogan et al .,[ 20 ] almost all other studies showed active hepatitis with varying severity in all the patients biopsied. Some of the studies had tried to correlate various variables with the degree of histological changes, however, data is limited.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In our cohort of 270 cases, only 1 patient showed histological cirrhosis. Except a study by Ozdogan et al .,[ 20 ] almost all other studies showed active hepatitis with varying severity in all the patients biopsied. Some of the studies had tried to correlate various variables with the degree of histological changes, however, data is limited.…”
Section: Discussionmentioning
confidence: 92%
“…There are limited numbers of studies on liver histology in patients on maintenance HD with HCV infection. After excluding studies that had clubbed dialysis and transplant patients,[ 17 18 19 ] we could find 9 studies between 1997 and 2011, which have reported liver histopathology in patients on maintenance HD[ 19 20 21 22 23 24 25 26 27 ] [ Table 2 ]. Of these 9 studies, 5 are from Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Allo stesso modo, anche nella nostra popolazione si confermano le note correlazioni tra epatite C e fattori di rischio quali, la dialisi extracorporea, le emotrasfusioni e i precedenti trapianti. Il rischio teorico di una più rapida progressione dell'epatite C indotta dall'immunosoppressione, la sostanziale impossibilità a utilizzare l'interferone dopo trapianto per l'elevato rischio di rigetto acuto (5), la correlazione tra severità delle lesioni istologiche pre-trapianto e l'evolutività dell'epatopatia (2) e l'assenza di una precisa correlazione tra dati biochimici e quadri istologici (6), hanno portato a suggerire la biopsia epatica come strumento utile per una corretta valutazione di idoneità al trapianto renale del paziente uremico con infezione da virus C. Tuttavia, non sono ancora disponibili dati definitivi che impongano l'utilizzo di questa procedura in tutti pazienti HCV-positivi (6,7). In questo studio è stato esaminato il quadro morfologico epatico presente in pazienti viremici (HCV-RNA+), che si presentavano al momento della valutazione per l'inserimento in lista trapianto con una normale funzione epatica, con o senza citolisi.…”
Section: Discussioneunclassified
“…HCV infection remains the most frequently recognized cause of liver damage in chronic kidney disease (CKD) patients [3,4]. Evidence accumulated in the last decade shows a link between HCV and reduced survival in patients on maintenance dialysis; the mechanisms underlying this relationship are an area of active research.…”
Section: Introductionmentioning
confidence: 99%